Design Posters and Infographics for Socialising Clean and Healthy Lifestyle in Gayungan Village Surabaya City - Ardani, Muhammad Widyan; Marsudi, Marsudi; Islam, Muh Ariffudin; Firmansyah, Novian (Proceeding of International Joint Conference on UNESA, 2025)
The Gayungan sub-district in Surabaya City has a flagship program that aims to improve the implementation of a clean and healthy lifestyle among its residents. Based on an interview with the Head of the Sub-district, Pramudita Yustiani, S.T., this program focuses on education regarding waste sorting, waste utilization, and the implementation of smoke-free areas. The results of observations through questionnaires show that 65% of the community has implemented clean and healthy living behaviors, while 35% has not. In addition, 55% of residents are not aware of the socialization program, while 45% are aware of it. To overcome this problem, the proposed solution is to develop media in the form of visually appealing posters and infographic guidebooks. This media is designed using a design thinking approach to ensure suitability with user needs and provide an optimal user experience. With clear instructions and appropriate visualizations, the information material can be more easily accepted by the lower-middle class. Overall, this study emphasizes the importance of effective visual design in conveying information and shows that the design thinking approach can produce media that is relevant to user needs, thereby increasing the effectiveness of socialization programs.